THE EFFECT OF THE MEDITERRANEAN DIET PATTERN ON CHOLESTEROL LEVELS AND CARDIOVASCULAR HEALTH IN URBAN ADULTS - N. Ai Erlinawati (INJOSEDU: International Journal of Social and Education, 2025)
Cardiovascular disease is one of the main causes of death in urban areas, which is triggered by unhealthy lifestyles, including unbalanced diets. The Mediterranean diet has been known as a dietary approach that is rich in healthy fats, fiber and antioxidants which play a role in maintaining heart health. However, its effectiveness in reducing cholesterol levels and improving cardiovascular health in urban communities still needs to be studied further. This research uses a systematic literature review method by analyzing various journals and scientific articles from trusted databases such as PubMed, ScienceDirect, and Google Scholar over the last 10 years. The collected data was analyzed thematically and comparatively to evaluate the impact of the Mediterranean diet on LDL, HDL cholesterol levels and the risk of cardiovascular disease. Studies show that the Mediterranean diet significantly lowers LDL levels, increases HDL levels, and reduces the risk of atherosclerosis. Additionally, this diet has been shown to be effective in reducing inflammation and improving blood vessel function, which contributes to a reduced risk of heart disease. Large studies such as PREDIMED support these findings by showing a 30% reduction in the risk of cardiovascular disease in individuals who adopt a Mediterranean diet. However, its implementation in urban areas faces challenges such as limited time, access to healthy food ingredients, and different eating habits. The Mediterranean diet has been proven to be beneficial in maintaining cardiovascular health and lowering cholesterol levels, making it an effective dietary strategy for urban communities. However, flexible adaptation is needed by considering the availability of local food ingredients and the lifestyle of urban communities so that this diet can be implemented sustainably.